2020
DOI: 10.1177/0886260520905552
|View full text |Cite
|
Sign up to set email alerts
|

Silent and Lethal: Consequences of Sexual Violence Against Married Women in Ghana

Abstract: Extant research, mostly in western countries, confirms the consequences of sexual violence against women, but academic scholarship on this topic remains scant for Ghana. This study built on existing research by exploring the consequences of sexual violence against married women in the Eastern Region of Ghana. Data were obtained from in-depth interviews purposely conducted with 15 survivors of sexual violence. The thematic analysis showed that sexual violence was accompanied by physical and emotional abuse. Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Ssewanyana et al highlighted the occurrence of genital trauma among adolescent girls resulting from sexual assault [ 14 ]. Apatinga et al demonstrated that sexual violence was accompanied by physical abuse, leading to physical injuries among women [ 15 ]. Azumah et al reported that visually impaired women who experienced gender-based violence faced a higher risk of injuries including genital injuries [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ssewanyana et al highlighted the occurrence of genital trauma among adolescent girls resulting from sexual assault [ 14 ]. Apatinga et al demonstrated that sexual violence was accompanied by physical abuse, leading to physical injuries among women [ 15 ]. Azumah et al reported that visually impaired women who experienced gender-based violence faced a higher risk of injuries including genital injuries [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“… • Genital trauma resulting from sexual assault was experienced by many adolescent girls. Apatinga et al, 2021 [ 15 ] Ghana To explore the consequences of sexual violence against married women in the Eastern Region • Following sexual violence and abuse, women experienced physical injuries. Azumah et al, 2019 [ 16 ] Ghana To find answers to GBV against visually impaired persons in the Kumasi and their experiences in relation to GBV • GBV had effects of battering against visually impaired women, leading to a greater risk of injuries such as genital injuries.…”
Section: Resultsmentioning
confidence: 99%
“…The same observation has been made by several authors. In Ghana and Brazil, sexual violence was also accompanied by physical and psychological violence [12,13]. Also in Nigeria, physical violence was the most common type experienced by women (58.1%) [14].…”
Section: Discussionmentioning
confidence: 99%
“…The same applies to feelings of shame and guilt, which often prevent victims from seeking help from health professionals [2,19]. In Ghana, women have suffered physical injuries, psychological problems, sexual and reproductive health problems and suicidal thoughts as a result of violence [12]. These health problems have significantly affected their economic activities and impoverished their income.…”
Section: Source Of Fundingmentioning
confidence: 99%
See 1 more Smart Citation